Nitrogen Dioxide Monitoring with Satellite Imagery over Ankara, Turkey - Maryam Zare Shahne; Mostafa Jazari; Zahra Amiri (Numerical Methods in Civil Engineering)
Earth observation satellites possess key characteristics such as high temporal and spatial resolution, wide coverage imaging, multispectral capabilities, and access to a rich archive of images through various gateways. This enables the regular and continuous monitoring of phenomena related to various pollutants on a global scale. Presently, weather models leverage satellite imagery to record and report pollutant levels hourly and daily, allowing for the identification of sources and patterns of pollutants. Remote sensing technology, with its ability to measure concentration and intensity, as well as track the movement and changes in pollutant locations, has multiple applications in assessing air quality. The use of this technology facilitates informed decision-making and expert analysis to reduce air pollution, contributing to the goal of achieving clean and healthy air on the planet. In this report, Sentinel 5 satellite data was utilized to monitor NO2 gas emissions in the city of Ankara. The data was analyzed month by month over the course of a year, providing valuable insights into the trends and patterns of NO2 concentrations.at the end of this article we will find that Google Earth Engine and remote sensing may replace ground stations, shifting their role to validation. The study finds high similarity in ground and satellite data, especially in analyzing NO2 concentration and its seasonality. Utilizing advanced satellite tech, like Google Earth Engine, emphasizes language and technology in addressing environmental challenges for a sustainable future